Time Poverty Among Women in Ondo State, Nigeria: An Emperical Analysis - OSUJI, JOY ADAEZE; OBISESAN, DR. MRS. ADEKEMI ADEBISOLA (Journal of Science, Technology and Innovation Research, 2026)
Time poverty, which is driven by gender roles and socioeconomic conditions, inhibits women’s economic empowerment and their capacity to engage in paid job, education, and career advancement . Rural communities have inadequate infrastructure and restricted access to energy, healthcare, clean water, and education, exacerbating inequality. Multistage sampling procedure was employed in the selection of 150 respondents from rural and urban communities. Primary data were obtained through the use of structured questionnaire. Data were analysed using descriptive statistics, Foster-Greer-Thorbecke (FGT) model and probit regression model. The result revealed that age group with the highest representation was 4150 years. Average ages were 38.05 years for urban women and 44.54 for rural women. Rural women, who worked mostly in informal, physically demanding jobs (92%), had higher time constraints than urban women (60%), although the latter were also experiencing time poverty due to unpaid family commitments. In addition, urban women spent a mean of 15.69 hours/day on various activities, while rural women spent a mean of 16.64 hours/day on various activities, with the overall mean of 16.17 hours/day on various activities indicating increased fatigue and stress on rural women. Using a time poverty threshold of 14.1 hour/day, 71.33% of the respondents were classified time poor. Time poverty was higher among rural women than their urban counterparts. This study applied a probit regression model to data from 150 women to examine time poverty. Age, household size and personal care were significant correlates of time poverty. Age reduced time poverty. Household size decreased time poverty. Personal care decreased time poverty. The study recommends improved rural infrastructure. KEY WORDS: Time poverty, Women, Ondo State, Nigeria.